Arterial enhancing‐only nodules less than 2 cm in diameter in patients with liver cirrhosis: Predictors of hepatocellular carcinoma diagnosis on gadobenate dimeglumine‐enhanced mr imaging. Issue 4 (23rd October 2012) - Quaia, Emilio; Pizzolato, Riccardo; De Paoli, Luca; Angileri, Roberta; Ukmar, Maja; Assunta Cova, Maria
Abstract Purpose: To assess whether gadobenate dimeglumine (Gd‐BOPTA)‐enhanced MR imaging could predict hepatocellular carcinoma (HCC) diagnosis in small arterial enhancing‐only nodules detected by contrast‐enhanced computed tomography (CT) in patients with liver cirrhosis. Materials and Methods: We prospectively recruited 125 cirrhotic patients (67 males, and 58 females; age: 68 ± 12.36 years) with 151 small (<2 cm in diameter) arterial enhancing‐only nodules identified by contrast‐enhanced CT. All patients were scanned by MR imaging before and after Gd‐BOPTA injection during the hepatic arterial phase (HAP), portal venous phase (PVP), equilibrium phase (EP), and hepatobiliary phase (HP). Nodule characterization was based on reference imaging criteria (n = 29 nodules), follow‐up (n = 105), or histology (n = 17). Two radiologists (5 and 10 years experience) analyzed the MR images, and logistic regression was conducted to assess how well MR imaging findings could predict HCC diagnosis. Results: Final diagnoses included 115 benign nodules and 36 HCCs. Nodule T2 hyperintensity, T1 hypointensity, PVP‐EP hypointensity, and HP hypointensity were the best predictors of HCC on univariate analysis. Nodule T2 hyperintensity, T1 hypointensity, and HP hypointensity, were independent predictors of HCC on multivariate analysis. Conclusion: Gd‐BOPTA‐enhanced MR imaging provides imaging findings which may predict a diagnosis of HCC in small arterial enhancing‐only nodules in cirrhotic patients. J. Magn. Reson. Imaging 2013;37:892–902. © 2012 Wiley Periodicals, Inc.